The comparison of creatinine and cystatin C value in preeclampsia severity and neonatal outcome - John Wantania; Abraham Winarto (Majalah Obstetri dan Ginekologi, 2016)
Objectives: to compare the levels of creatinine and cystatin C with the severity of preeclampsia, and assess neonatal outcomes.Materials and Methods: Creatinine, cystatin C, and neonatal outcomes were assesed in 17 normotensive samples, 17 samples of mild preeclampsia and 17 samples of severe preeclampsia. Analysis of data with statistical tests of ANOVA and t test differences between 2 proportions.Results: The mean levels of creatinine in the normotensive group, mild preeclampsia, severe preeclampsia are 0.56 mg/dL, 0.67 mg/ dL, and 0.75 mg/dL, p=0.138; While on cystatin C are 0.82 mg/L, 1.03 mg/L and 1.32 mg/L, p=0.000. The adverse neonatal out-come wasn’t found in the normotensive group. In mild pre-eclampsia obtained 1 preterm birth and 1 intrauterine fetal death (IUFD), whereas in severe preeclampsia obtained 3 babies born preterm, 1 IUFD, and 1 intrauterine growth restriction (IUGR).Conclusion: levels of cystatin C was increased significantly in line with increased severity of preeclampsia, whereas creatinine was not increased significantly. Cystatin C is better than crea-tinine as a marker of renal dysfunction in preeclampsia patients. There was an increase in adverse neonatal outcomes in the group of preeclampsia.